Droplet interface bilayer reconstitution and activity measurement of the mechanosensitive channel of large conductance from Escherichia coli - Barriga,HMG; Booth,P; Haylock,S; Bazin,R; Templer,RH; Ces,O (Journal of the Royal Society Interface, 2014)
Droplet interface bilayers (DIBs) provide an exciting new platform for the study of membrane proteins in stable bilayers of controlled composition. To date, the successful reconstitution and activity measurement of membrane proteins in DIBs has relied on the use of the synthetic lipid 1,2-diphytanoyl-sn-glycero-3-phosphocholine (DPhPC). We report the functional reconstitution of the mechanosensitive channel of large conductance (MscL) into DIBs composed of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), a lipid of significantly greater biological relevance than DPhPC. MscL functionality has been demonstrated using a fluorescence-based assay, showing that dye flow occurs across the DIB when MscL is gated by the cysteine reactive chemical 2-(trimethylammonium)ethyl methane thiosulfonate bromide (MTSET). MscL has already been the subject of a number of studies investigating its interaction with the membrane. We propose that this method will pave the way for future MscL studies looking in detail at the effects of controlled composition or membrane asymmetry on MscL activity using biologically relevant lipids and will also be applicable to other lipid–protein systems, paving the way for the study of membrane proteins in DIBs with biologically relevant lipids.